Improving the treatment of infant pain - Moultrie, F; Slater, R; Hartley, C (Lippincott, Williams & Wilkins, 2017)
Purpose of review: Pain management presents a major challenge in neonatal care. Newborn infants who require medical treatment can undergo frequent invasive procedures during a critical period of neurodevelopment. However, adequate analgesic provision is infrequently and inconsistently provided for acute noxious procedures, due to limited and conflicting evidence regarding analgesic efficacy and safety of most commonly used pharmacological agents. Here we review recent advances in the measurement of infant pain and discuss clinical trials that assess the efficacy of pharmacological analgesia in infants. Recent findings: Recently developed measures of noxious-evoked brain activity are sensitive to analgesic modulation, providing an objective quantitative outcome measure that can be used in clinical trials of analgesics. Summary: Noxious stimulation evokes changes in activity across all levels of the infant nervous system, including reflex activity, altered brain activity and behaviour, and long-lasting changes in infant physiological stability. A multimodal approach is needed if we are to identify efficacious and safe analgesic treatments. Well-designed clinical trials are urgently required to improve analgesic provision in the infant population.